Kupiah Riman Ornament Motif as a Cultural Representation of the Acehnese Community - Ismawan Ismawan; Tri Supadmi; Tengku Hartati; Lindawati Lindawati (Proceedings of AICS - Social Sciences, 2021)
The research entitled